2022
DOI: 10.3390/en15051871
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Variant Modal Analysis Approach for Large Industrial Machine

Abstract: Power generation technologies are essential for modern economies. Modal Analysis (MA) is advanced but well-established method for monitoring of structural integrity of critical assets, including power ones. Apart from classical MA, the Operational Modal Analysis approach is widely used in the study of dynamic properties of technical objects. The principal reasons are its advantages over the classical approach, such as the lack of necessity to apply the excitation force to the object and isolate it from other e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…So far, the research has confirmed two standard methods for extracting modal parameters, including operational modal analysis (OMA) as well as experimental modal analysis (EMA) [71,72]. When comparing the two methods, each has benefits and drawbacks.…”
Section: Tbs Modal Parameters' Extraction Methodsmentioning
confidence: 97%
“…So far, the research has confirmed two standard methods for extracting modal parameters, including operational modal analysis (OMA) as well as experimental modal analysis (EMA) [71,72]. When comparing the two methods, each has benefits and drawbacks.…”
Section: Tbs Modal Parameters' Extraction Methodsmentioning
confidence: 97%
“…More recent studies carried out by [5] showed that even the turbulent gas flow within the seals of a turbomachine can be used to excite the system and identify the modal parameters via OMA, demonstrating OMA's potential for condition monitoring. Moreover, in [6] it was verified that a hybrid approach based on both OMA and EMA was able to diagnose a vibration problem in a large rotating machine used in the power generation industry. It is important to highlight that OMA was used to identify that a resonance frequency was causing the problem.…”
Section: Introductionmentioning
confidence: 90%